Perbandingan Daya Dukung Aksial Tiang Pancang Tunggal Berdasarkan Data Sondir dan Data Standard Penetration Test - Immanuel Panusunan Tua Panggabean (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2017)
Axial bearing capacity of piles can be obtained by using the data from the data Sondir or data from Standard Penetration Test (SPT). Calculation using the Direct Method for data Sondir and Meyerhof method and  method to data from Standard Penetration Test (SPT), a lot is done to determine the axial bearing capacity of piles. Selection of axial bearing capacity of piles used results of these calculations into a separate art for planners to determine the dimensions of the foundation are used